Structural analysis of the interaction between the human immunodeficiency virus Rev protein and the Rev response element. - Kjems, J (1991)
The specific interaction between a defined structural element of the human immunodeficiency virus mRNA (RRE, the Rev response element) and the virus-encoded protein Rev has been implicated in the regulation of the export of unspliced or singly spliced mRNA from the nucleus to the cytoplasm. Rev protein was expressed and purified from insect cells using the baculovirus expression system. Chemical and RNase probes were used to analyze the structure of the RRE and the regions involved in Rev binding. Increased reactivity to single-strand-specific probes of nucleotides in two helical domains indicates that Rev binding induces conformational changes in the RRE. Binding of Rev to the RRE primarily protects helical segments and adjacent nucleotides in domain II. A Rev unit binding site is proposed that consists of a six-base-pair helical segment and three adjacent nucleotides. The data also suggest that multiple Rev proteins bind to repeated structural elements of the RRE.